Brief Overview of MERS: Middle East Respiratory Syndrome - Ayesha Nadeem; Hafiza Arshi Saeed; Ambreen Talib; Rabbya Rayan Shah; Rameen Atique; Abdul Samad (Journal of World Science, 2024)
Middle East Respiratory Syndrome (MERS) is a zoonotic disease caused by MERS-CoV, a beta coronavirus with a mortality rate of approximately 35%. The disease exhibits a wide range of clinical symptoms, from mild respiratory issues to severe conditions like multi-organ failure and pneumonia. Person-to-person transmission has led to significant hospital and community outbreaks, underscoring the urgent need for effective infection control measures. This study explores MERS-CoV's epidemiology, pathogenesis, and transmission dynamics, aiming to enhance understanding of its replication, spread, and control strategies due to limited pharmaceutical interventions. A comprehensive review of current literature was conducted, focusing on epidemiological data, genetic characteristics, and transmission patterns across affected regions, including the Middle East, Asia, Africa, and North America. Findings indicate that MERS-CoV originated from recombination events in the spike protein of African dromedaries and spread to the Arabian Peninsula via camels. The virus affects not only humans but also domestic animals like sheep, cattle, horses, and pigs, with global transmission facilitated by travelers, resulting in outbreaks in Asia and North America. Despite extensive research, no effective vaccines, antiviral drugs, or immune therapies control MERS-CoV. The findings emphasize the high pandemic potential of MERS-CoV due to its mortality rate and lack of effective treatments, highlighting the need for strict infection control and further research into viable therapeutic options.